From Urban Stress to Neurourbanism: How Should We Research City Well-Being?. Issue 6 (1st November 2020) - Pykett, Jessica; Osborne, Tess; Resch, Bernd
Abstract : Urbanicity has long been associated with stress, anxiety, and mental disorders. A new field of neurourbanism addresses these issues, applying neuroscience laboratory methods to tackle global urban problems and promote happier and healthier cities. Exploratory studies have trialed psychophysiological measurement beyond laboratories, capitalizing on the availability of biosensing technologies to capture geo-located physiological markers of emotional responses to urban environments. This article reviews the emerging conceptual and methodological debates for urban stress research. City authorities increasingly favor new data-driven and technology-enabled approaches to governing smart cities, with the aim that governments will be enabled to pursue evidence-based urban well-being policies. Yet there are few signs that our cities are undergoing the transformative, structural changes necessary to promote well-being. To face this urgent challenge and to interrogate the technological promises of our future cities, this article advances the conceptual framework of critical neurogeography and illustrates its application to a comparative international study of urban workers. It is argued that biosensing data can be used to elicit socially and politically relevant narrative data that centers on body–mind–environment relations but exceeds the individualistic and often behaviorist confines that have come to be associated with the quantifying technologies of the emerging field of neurourbanism.